Prepositions in their syntactic, semantic, and pragmatic context - Feigenbaum, Susanne; Kurzon, Dennis (J. Benjamins Pub., 2002)
The growing interest in prepositions is reflected by this impressive collection of papers from leading scholars of various fields. The selected contributions of Prepositions in their Syntactic, Semantic and Pragmatic Context focus on the local and temporal semantics of prepositions in relation to their context, too. Following an introduction which puts this new approach into a thematical and historical perspective, the volume presents fifteen studies in the following areas: The semantics of space dynamics (mainly on French prepositions); Language acquisition (aphasia and code-switching); Artif.
Keywords: Grammar, Comparative and general -- Prepositions.; Grammar, Comparative and general -- Syntax.; Semantics.; Pragmatics.; Semantics; Prépositions.; Syntaxe.; Sémantique.; Pragmatique.; semantics.; pragmatics.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Grammar, Comparative and general -- Prepositions; Grammar, Comparative and general -- Syntax; Pragmatics; Voorzetsels.; Electronic book.